Adherence to Oral Anticoagulants in Atrial Fibrillation: An Australian Survey - Obamiro, K.; Chalmers, Leanne; Lee, K.; Bereznicki, B.; Bereznicki, L. (2018)
© 2018, The Author(s) 2018. Background: The aim of this study was to investigate the proportion of patients who have suboptimal adherence to oral anticoagulant (OAC), identify the predictors of adherence, and determine whether patient-related factors vary across adherence levels in Australia. Methods: Respondents were recruited for an online survey using Facebook. Survey instruments included the Morisky Medication Adherence Scale, the Anticoagulation Knowledge Tool, the Perception of Anticoagulant Treatment Questionnaires, and a modified Cancer Information Overload scale. Predictors of medication adherence were identified using ordinal regression analysis. Results: Of the 386 responses eligible for analysis, only 54.9% reported a high level of adherence. Participants aged 65 years or younger were less likely to have high adherence compared to older participants (odds ratio [OR], 0.54; 95% confidence interval [CI] , 0.33-0.88; P =.013), while females were more likely to be highly adherent compared to males (OR, 1.69; 95% CI, 1.08-2.64; P =.023). The analyses showed that age, gender, treatment satisfaction, information overload, concerns about making mistake when taking OACs, and cost of medication were significant predictors of adherence. Conclusion: Self-reported suboptimal adherence to OAC is common among patients with atrial fibrillation. A focus on supporting people who are at higher risk of suboptimal adherence is needed to maximize the benefit of OAC therapy in this population.